а) х - 2у = 5 7х - 3у = 13 х = 2у + 57(2у + 5) = 1314у + 35 = 1314у = - 22у = - 22/14 = - 11/7х = 2 * (- 11/7) +5 = - 22/7 +5 = (- 22 + 35)/7 = 13/7б) 3х - 2у = 12 4х + у = 5у = 5 - 4х3х - 2(5 - 4х) = 12 3х - 10 + 8х = 1211х = 22х = 2у = 5 - 4*2 = 5 - 8 = - 3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
а) х - 2у = 5
7х - 3у = 13
х = 2у + 5
7(2у + 5) = 13
14у + 35 = 13
14у = - 22
у = - 22/14 = - 11/7
х = 2 * (- 11/7) +5 = - 22/7 +5 = (- 22 + 35)/7 = 13/7
б) 3х - 2у = 12
4х + у = 5
у = 5 - 4х
3х - 2(5 - 4х) = 12
3х - 10 + 8х = 12
11х = 22
х = 2
у = 5 - 4*2 = 5 - 8 = - 3